Status, Distribution and Potential Habitat of Himalayan Tahr (Hemitragus jemlahicus), and Conflict Areas with Livestock in Sagarmatha National Park, Nepal - Shrestha, Bikram (Nepal Journal of Science and Technology, 2007)
Study on status, distribution and potential habitat of Himalayan tahr (Hemitragus jemlahicus), and conflict areas with livestock in Sagarmatha National Park, Nepal was carried out from 21th June to 14th July 2004 in Sagarmatha National Park, which is important for conservation of this animal, pastureland and snow leopard. The numbers of tahr sighted, their age/sex, and distance to escape terrain and habitat variables were collected from five scan points and four transects. Grazing pasturelands were identified by field visits and questionnaire survey. Maps of potential habitat suitability and areas of spatial overlap with livestock were prepared by using geographical information system (GIS). A total population of 205 tahrs within 11 groups was estimated in the park. Tahrs were recorded at various altitudes ranging from 3685 to 4380 m with a mean elevation of 4059.18 m. The male groups were found at higher elevation than female groups, and the latter had larger group sizes. The overall mean group size was 18.7 with 45 being the largest group. Normally more number of tahrs were found on smooth terrain of vegetated surface on southern aspects. All observations ranged from 50 to 200 m distances from a escape terrain. An analysis on potential habitat of the tahr revealed the occurrences of 56442.5 ha of land surface in the protected area of which summer habitat covers 29483.25 ha, winter habitat with 4064.0 ha and overlapping areas of summer and winter accounts amounts to 22895.25 ha. The present analysis showed 17.43% of the total potential areas of the Himalayan tahr is under conflict inside the park. Nepal Journal of Science and Technology Vol. 7, 2006